Miectomía frontal: Una alternativa para reducir arrugas frontales - Viterbo, Fausto [UNESP]; Nduka, Charles; Brock, Ryane S. [UNESP] (My University, 2017)
Background and Objective. The skin, subcutaneus and osseus changes over time are characteristic of the ageing face. Loss of soft tissue elasticity, volumetric changes, and facial muscular activity are largely responsible for facial wrinkles, and is the treatment of these that are the most frequent request of patients wanting to look younger. The objective of this study is to describe an alternative surgical technique to treat frontal wrinkles with less morbidity and longer results. Methods. Thirty-one patients from 37 to 75 years old were submitted to frontal miectomy from 2003 to 2007. The incision was divided on superior eyelid, pre-capilar and transcapilar. Results. Patients submitted to this technique had short recovery time with edema around 5 to 7 days. They returned to their normal activities in 7 days. No patients had intra or postoperative complications. All patients were satisfied with the result. Conclusions. Frontal horizontal wrinkles treatment with frontal miectomy is a quick and minimally invasive procedure, with a long term result.
Frontal muscle miectomy: An alternative to reduce frontal wrinkles
Keywords: Facial wrinkles; Frontal rhytidectomy; Miectomy